Plasma Calprotectin Levels in Preeclamptic Normotensive Pregnant and Nonpregnant Women - Akçum, Sedat; Zülfikaroğlu, Ebru; Eserdağ, Süleyman; Özcan, Utku (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: To compare the changes in plasma calprotectin levels in women with preeclampsia, late normal pregnancy and nonpregnant women. STUDY DESIGN: A total of 30 preeclamptic patients were included in the study, 30 normotensive uncomplicated pregnant patients and 20 nonpregnant patients were taken as control groups. Plasma levels of calprotectin were analyzed using an enzyme-linked immuno-sorbent assay. RESULTS: Significantly higher levels of maternal plasma calprotectin in preeclamptic group were discovered 783 (478- 928) μg/L, compared to normotensive pregnant control 618 (343- 887) μg/L and the nonpregnant women 574 (283- 797) μg/L (P=0.001). Further, plasma level of calprotectin was significantly higher in severe preeclampsia 954 (691- 985) μg/L than mild preeclampsia 589(492- 712) μg/L (p=0.037). Compared with pregnant control, the plasma level of mild or severe preeclampsia was significantly elevated (p= 0.047 and 0.012, respectively). CONCLUSION: Elevated maternal plasma calprotectin level was demonstrated in preeclampsia suggesting that preeclampsia may represent an excessive maternal inflammatory response to pregnancy and calprotectin may contribute the pathogenesis of this disorder.